African intellectuals - Mkandawire, Thandika (New York Zed Books, 2005)
African intellectuals today face uniquely difficult circumstances - intolerant regimes, economies in sharp decline, societies wracked by violent conflict, and official languages that are not mother tongues. Compared with Asia or Latin America, Africa has experienced much higher rates of emigration of its intelligentsia to North America and Europe, and frequent displacement within the continent. This rare overview of their history, fate and future roles explores the relationship of African intellectuals to nationalism and the Pan African project; the indigenous language question; women intellectuals; and the role of the hugely growing African academic diaspora. It assesses the interface between African intellectuals and society, state and politics in the context of the restoration of multi-party politics, changing economic policies, and renewed Pan African awareness.
Includes bibliographical references and index.
Keywords: Africa -Intellectual life -Congresses.